Selenium with Python - A Beginner's Guide Get started with Selenium using Python as a programming language - R Sharma, Pallavi; R Sharma, Pallavi (BPB Publications, 2019)
Step by step directions to get started with Selenium using Python as a programming language. Key FeaturesGet introduced to the world of Selenium Understand the concept of locators in Selenium Learn how to write scripts using Selenium WebDriver in PythonLearn the concepts of synchronization Learn how to handle different HTML elements like form, table, alert, frame, and dropdown Learn about design patterns like the page object model, data-driven tests, and adding assertions. DescriptionSelenium is the most popular open source test automation tool available in the market. In the last decade, its usage has dramatically increased in the IT sector across all types of organizations. The reason for its popularity is mainly because it supports multiple programming languages, test executions on multiple browsers and operating systems. In this book, we will learn about the different components of Selenium. We will discuss the concepts of WebDriver and learn how to apply test automation concepts with it to automate the testing of our application. We will learn the process of recognizing the test objects on the screen and writing Selenium commands using Python as a programming languageWe will also discuss how to use design patterns like the page object mode and data-driven testing to ensure building a robust test framework, which is modular and scalable in nature. What You Will LearnThe objective is to introduce the world of Selenium to a manual tester who knows Python as a programming language. You will learn to demystify the concept of identifying test objects and writing Selenium commands to create robust test scripts. This book will help learn to automate different HTML elements, which we come across in the web applications we need to test. You will understand how to build a good test suite by learning the concept of design patterns like the page object model and data-driven tests to ensure maintainability of code. Who this book is forThis book is for people who have experience in manual testing and knowledge in Python as a programming language. This book will also be helpful for a developer who knows Python as a programming language and is looking for test automation as a career option. Table of Contents 1. Selenium - Important Conceptual Background 2. Selenium IDE 3. Locators in Selenium 4. Installation and Setup 5. Selenium WebDriver 6. Unit Test Creation n Python 7. Synchronizing Tests 8. Parameterization of Tests 9. Handling Different Web Elements 10. Working with Frames 11. Concept of the Page Object Model 12. Implementing Selenium Grid About the AuthorPallavi has an overall professional experience of 14 years. She has worked in varied roles as a product/project manager in the presales team and marketing team for solutions on test automation tools.She holds two provisional patents along with other contributors for her work on building tool agnostic test automation framework solutions. Currently, she is acting as a test automation coach, writer, speakerand owner at 5 Elements Learning where she collaborates and works with test automation enthusiasts across the globe. As an avid learner, she likes to keep herself updated to the latest trends andTechnologies. She is a firm believer in a larger good and likes to live by example.She volunteers her time for the organization eVidyaloka where she acts as a centre administrator. She is a lifetime member for the Jabarkhet forest reserve and People for Animals.Website: http://5elementslearning.comLinkedIn Profile: https://www.linkedin.com/in/pallavirsharma